War in the Novels of Abroad Iraqi Women Between 2003 - 2010 - داود سلمان العنبكي غادة جمال مكي (College of Education for Women, 2019)
This research dealt eith the effect of wars experienced bythe Iraqi people in the abroad Iraq women novels between 2003 - 2010, where this issye dominated on Iraqi women novels at this stage until it became the main subject that events revolved aroud in the novels of this stage. The research also highlighted on the impact of continuous tough wars in human life and psyche, especially in the lives of women - and this is the privacy of feminist novel - where the Iraqi women novels focused on the impact of war on psychological of women and what it caused of misfortunes as women. Iraqi women have suffered from the bitterness of the loss caused by war as - any loss - a natural of her - the loss of father, son, husband, brother and lover - . And that what well try to demonstrate on this research.